Development of a thermo diagnostic device for monitoring the technical condition of bearings and its comparison with other control methods - Ozolins, Eriks; Orlov, Anton; Ozolins, Ilmars (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Within the Institute of Aeronautics, a working diagnostic device was developed, which is able to perform remote temperature monitoring of bearings with a set periodicity, as well as warns the technical staff about temperature rises above the operating limit. The article describes the components of the device and the conditions for their selection. Relatively long-term experimental tests were performed to fully test the device and verify its performance. In the course of these tests, a comparison of the developed device with other bearing control devices was also made in order to be able to draw conclusions as to whether our device is effective in controlling the technical condition of bearings. This article summarizes the results of these researches.